A dimensão do desenho nas esculturas de Evandro Soares - Sampaio, Glayson Arcanjo de (2019)
This article describes Brazilian artist Evandro Soares’s poetic process. It discusses the procedures applied when working with metallic material (iron and wire) through welding, cutting and bending techniques in order to create complex geometries in his produced sculptures. This process points out the characteristic of his sculptures being simultaneously as spatial drawings or linear sculptures since they converge in the same exhibition space particular situations and two-dimensional and three-dimensional features